2010
DOI: 10.1080/09687769.2010.492848
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability factors for e-learning initiatives

Abstract: This paper examines the challenges that 'grass roots' e-learning initiatives face in trying to become sustainable. A cross-institutional study focused on local, rather than centrally driven, initiatives. A number of successful e-learning innovations were identified that had been driven by capable teachers seeking solutions to real educational problems. However, most of these remain in a high-risk category for institutions and offer poor rewards to their creators. While they may attract grant funding, these ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 10 publications
5
59
0
1
Order By: Relevance
“…Therefore, it seems necessary to provide proper support for lecturers who want to be involved in e-learning courses and to supply adequate and reliable infrastructure, in order to increase the number of courses offered in an e-learning module. There is a need for systemic support for lecturers engaged in the implementation of online courses, as without relevant administrative and technical support a large amount of academics are skeptical about using e-learning for their courses [49]. Universities can increase the number of e-learning courses if the academic staff do not have to face a variety of problems related to the implementation and administration of online modules [24].…”
Section: Educators' Approach To E-learningmentioning
confidence: 99%
“…Therefore, it seems necessary to provide proper support for lecturers who want to be involved in e-learning courses and to supply adequate and reliable infrastructure, in order to increase the number of courses offered in an e-learning module. There is a need for systemic support for lecturers engaged in the implementation of online courses, as without relevant administrative and technical support a large amount of academics are skeptical about using e-learning for their courses [49]. Universities can increase the number of e-learning courses if the academic staff do not have to face a variety of problems related to the implementation and administration of online modules [24].…”
Section: Educators' Approach To E-learningmentioning
confidence: 99%
“…There are three e-learning modes of engagement, which correspond to growing levels of complexity and depth in LMS usage (see Figure 1) [15]. A cross-institutional study revealed both institutional and cultural barriers for e-learning to transform, rather than sit uncomfortably alongside, institutional practice [17]. Previous studies had found that most universities were at mode 1 of the Francis and Raftery model [7].…”
Section: Mobile Learning and Lmsmentioning
confidence: 99%
“…The role of individual pioneering staff is fundamental to the long-term sustainability of the OER movement, but institutions need to provide support and resources to embed OER into educational practices (Atkins, Brown, and Hammond 2007). As with e-learning in general, a sustainable approach requires cultural and institutional change, where staff share visions and are supported by organisational structures (Gunn 2010). In theory, the emergence of strong communities will provide a self-fulfilling prophecy, providing a community of producers, users and re-users (Dholakia, King, and Baraniuk 2006) and also providing a motivational force to sharing work (Larsen and Vincent-Lancrin 2005).…”
Section: Oer Moving Forwardsmentioning
confidence: 99%